RETRACTED: Methods for building ontologies to ensure coordinated behavior of autonomous intellectual systems in agriculture - Bzhikhatlov Kantemir; Pshenokova Inna; Nagoeva Olga (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001